Site-adapted production of bioenergy feedstocks on poorly drained cropland through the cultivation of perennial crops. A feasibility study on biomass yield and biochemical methane potential. (December 2018) - Ruf, Th.; Emmerling, C.
Abstract: Soil compaction depicts a major threat to soil fertility in extensive maize cultivation systems on soils that show conditions of waterlogging in autumn. Perennial energy crops may reduce the vulnerability for soil compaction by earlier harvest dates and improved soil stability. However, the performance of such crops to be grown on Stagnosols and Planosols is currently an open issue. Within the framework of a two-year experiment, we investigated the potential of five perennial energy crops and maize to be cultivated under periodically waterlogged soil conditions and effects on biomass and biomethane yield. Dry matter yields of perennial energy crops were 50% – 100% higher compared to maize. Contrarily, maize showed a weak yield performance under pronounced waterlogged conditions. Biochemical methane potentials were approx. 310 LN CH4 kg −1 VS for maize and on average 275 LN CH4 kg −1 VS for perennial energy crops, whereby different soil moisture regimes had no significant influence. Thus, our results reveal first indication for a sustainable biomass production on soils with periodically waterlogged conditions through the cultivation of perennial energy crops. Highlights: Performance of 5 perennial energy crops under periodically excess soil water. 2-year pot experiment incl. Cup Plant, Tall Wheatgrass, Jerusalem Artichoke etc. Indication of high yield potential of perennial energy crops. Weak growth of maize under pronounced waterlogged soil conditions. No effects of excess soil water conditions on biochemical methane potential.